Development of novel integrated pest management strategies against wireworms (Agriotes spp.) in French corn - Pierre Bourdon (2023)
Wireworms, the larvae of the click beetle are a major polyphagous soil pest, damaging crops such as corn, wheat, or potatoes. The withdrawal of registration of many chemical insecticides left farmers with a limited number of solutions against wireworms and soil pests. Entomopathogenic fungi (EPF) can be useful against wireworm; yet they are slow acting and species dependent. To override these limitations, stress and kill strategies were tested, combining spinosad and different Metarhizium strain against three different wireworm species from the genera Agriotes. Combining spinosad and M. brunneum could increase the mortality of the EPF strains; yet, the susceptibility of the Agriotes species differs for each combination (Chapter I). The aim of the PhD was to develop new integrated pest management strategies against wireworms to avoid important corn yield losses. Developing pest management strategies using EPF seemed unreliable; thus, fungal volatile organic compounds (VOCs) were tested for their fumigant and attractant/ repellent activity (Chapter II and III). In Chapter II, fumigation using 1-octen-3-ol and 3-octanone was tested against wireworm (Agriotes lineatus), corn rootworm (Diabrotica virgifera virgifera) and garden chafer (Phyllopertha horticola). The VOCs were highly efficacious in a closed environment (Chapter II); yet, in open containers, no mortality was observed (Chapter III). In this experiment, the VOCs had attractant/ repellent properties depending on the species. In silico study, confirmed that corn rootworm could detect and recognize the VOCs with their odorant binding proteins. As odorant binding proteins are well conserved between species, it is expected that wireworm and garden chafer can also detect and recognize the VOCs. In chapter IV, the VOCs were formulated as slow-release granules. These granules facilitate application of the VOCs in the field and increase the remanence of the VOCs in the soil. In fact, to avoid economic damage, wireworms need to be repelled from maize seedlings during the three first weeks of growth. Four doses of 1-octen-3-ol cyclodextrin granules were tested to reduce wireworm damage on maize. The lowest dose (2.26kg/ha) was attractive and increased damage; but doses of 4.52kg/ha or higher, significantly reduced damage for 18 days. The granule formulation needs to be optimized to increase the duration of the protection, but early indications suggest that VOCs granules appear to be a possible candidate to achieve wireworm control.